2015
DOI: 10.1002/bkcs.10031
|View full text |Cite
|
Sign up to set email alerts
|

A New Diol Ester Derivative of Dinophysistoxin‐1 from Cultures of Prorocentrum lima Collected in South Korea

Abstract: Keywords: Prorocentrum lima, Dinophysistoxin-1, DTX-1 diol ester, Cytotoxicity Marine dinoflagellates have been widely studied because of their rich chemodiversity and biologically toxic compounds extracted from them. These organisms are considered the cause of most occurrences of food poisoning from seafood. 1-3 Among these, the genera Prorocentrum and Dinophysis were well known to produce diarrhetic shellfish poisoning (DSP) toxins such as the okadaic acid (OA), pectenotoxin-2 (PTX-2), and dinophysistoxin-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Benthic dinoflagellates of the Prorocentrum genus, found in temperate and tropical waters, are a source of diarrhetic shellfish poisoning (DSP) toxins, such as okadaic acid (OA), dinophysistoxin-1 (DTX-1), and their analogues. In addition to DSP toxins, a variety of bioactive compounds have been isolated from cultured Prorocentrum species, e.g., prorocentrolides, , spiro-prorocentrimine, hoffmanniolide, prorocentrin, formosalides A and B, belizentrin, belizeanolide, prorocentrol, and limaol . Among these compounds, prorocentrolides and spiro-prorocentrimine are characterized by the presence of a cyclic imine (CI) group.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Benthic dinoflagellates of the Prorocentrum genus, found in temperate and tropical waters, are a source of diarrhetic shellfish poisoning (DSP) toxins, such as okadaic acid (OA), dinophysistoxin-1 (DTX-1), and their analogues. In addition to DSP toxins, a variety of bioactive compounds have been isolated from cultured Prorocentrum species, e.g., prorocentrolides, , spiro-prorocentrimine, hoffmanniolide, prorocentrin, formosalides A and B, belizentrin, belizeanolide, prorocentrol, and limaol . Among these compounds, prorocentrolides and spiro-prorocentrimine are characterized by the presence of a cyclic imine (CI) group.…”
supporting
confidence: 69%
“…In particular, stererochemical studies on these compounds have not been reported, except for the partial determination of the relative configuration of prorocentrolide B . In the course of exploring cytotoxic compounds from P. lima cultures, we isolated cytotoxic OA, DTX-1, and OA/DTX-1 analogues and limaol. , Recently, two prorocentrolides, namely, 4-hydroxyprorocentrolide ( 1 ) and prorocentrolide C ( 2 ), were identified in the polar fractions of the same P. lima extract. Herein, we clarify the planar structures of these two compounds and determine the relative configurations of their stereocenters by spectroscopic techniques.…”
mentioning
confidence: 99%
“…1,2 Prorocentrum is a representative genus that produces diarrhetic shellfish poisoning (DSP) toxins, such as okadaic acid (OA), dinophysistoxin-1 (DTX-1), and analogues. 3 Apart from these compounds, skeletally diverse bioactive compounds have also been isolated from cultured Prorocentrum species, including prorocentrolide, 4 spiro-prorocentrimine, 5 hoffmanniolide, 6 prorocentin, 7 formosalides A and B, 8 belizentrin, 9 belizeanolide, 10 and prorocentrol. 11 In our search for bioactive compounds from cultured P. lima, a new polyhydroxy compound, limaol (1), was isolated by cytotoxicity-guided fractionation.…”
mentioning
confidence: 99%
“…Moreover, the orientations of H-20 and H-24 on this skeleton were determined to be equatorial and axial, respectively, from the coupling constants of the well-split neighboring proton signals: J = 2.7 Hz between H-20 and H-21 and J = 9.1 Hz between H-23 and H-24. Further ROESY correlations of H-17/H-19a, H-17/H-19b, and H-14/H-22 allowed determination of the relative orientation of the octahydropyrano[3,2-b]pyran and dihydropyran rings.On the other hand, the configurations of the stereogenic centers beyond C-25 were established by measurement of3 J HH values from the DQF-COSY and 2,3 J CH values from the HECADE spectra and observation of ROESY correlations. As shown in Figure3A, the coupling constants related with H-25, H-26a, and H-26b, in accordance with JBCA, determined the orientation of the two nonequivalent protons on C-26.…”
mentioning
confidence: 99%
See 1 more Smart Citation